2014
DOI: 10.1016/j.neuroimage.2014.06.029
|View full text |Cite
|
Sign up to set email alerts
|

An automatic framework for quantitative validation of voxel based morphometry measures of anatomical brain asymmetry

Abstract: The study of anatomical brain asymmetries has been a topic of great interest in the neuroimaging community in the past decades. However, the accuracy of brain asymmetry measurements has been rarely investigated. In this study, we propose a fully automatic methodology for the quantitative validation of brain tissue asymmetries as measured by Voxel Based Morphometry (VBM) from structural magnetic resonance (MR) images. Starting from a real MR image, the methodology generates simulated 3D MR images with a known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…They can be used, for example, as priors during tissue segmentation or to mask functional MRI analysis to only gray matter. Haiko89 is also accompanied with the first symmetric baboon brain template (Haiko89_Sym), which provides researchers with the means to conduct voxel-based brain lateralization research in the baboon that is free from the confound created by normalizing to an asymmetric template (Fonov et al, 2011;Pepe et al, 2014). Furthermore, Haiko89 is the only available skull stripped baboon brain template that includes the olfactory bulb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be used, for example, as priors during tissue segmentation or to mask functional MRI analysis to only gray matter. Haiko89 is also accompanied with the first symmetric baboon brain template (Haiko89_Sym), which provides researchers with the means to conduct voxel-based brain lateralization research in the baboon that is free from the confound created by normalizing to an asymmetric template (Fonov et al, 2011;Pepe et al, 2014). Furthermore, Haiko89 is the only available skull stripped baboon brain template that includes the olfactory bulb.…”
Section: Discussionmentioning
confidence: 99%
“…For both human and non-human primate brains, it is well known that there are differences in morphology across the two cerebral hemispheres (e.g., Barrick et al, 2005;Pilcher et al, 2001). Symmetric templates are critical when investigating these hemispheric differences using, for example, voxel-based morphometry (VBM, Ashburner and Friston, 2000); normalization to an asymmetric template introduces a confound as it is impossible to conclude whether hemispheric differences are real or simply caused by normalization to an asymmetric template (Fonov et al, 2011;Pepe et al, 2014). Fourth, to our knowledge there are no tissue probability maps available to aid in the normalization or the segmentation of baboon brains.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 and Figure 5A illustrate a potential laterality effect on GM rate of atrophy that was not investigated in the present study since the methodological design used here did not allow us to statistically test for differences between the left and right hemispheres. Indeed, the 3C-MRI template used for spatial normalization was not a symmetrical one, and use of asymmetrical templates for both spatial normalization and segmentation is known to introduce biases in the study of hemispheric anatomical features [63] . Moreover the AAL parcellation used to estimate the regional GM rate of atrophy is also asymmetric.…”
Section: Discussionmentioning
confidence: 99%
“…Using deformation parameters calculated by the DARTEL toolbox, the gray matter images were normalized to MNI space and smoothed with a Gaussian kernel (FWHM = 8 mm). We set FWHM at 8 mm because the value was widely used (for review, see Nickl-Jockschat et al, 2012) and previous studies demonstrated that this size of spatial smoothing would improve the accuracy of VBM (Pepe et al, 2014) without increasing false-positive rates (Scarpazza et al, 2015). This preprocessing using DARTEL Toolbox included a modulation process to preserve the volume of a particular tissue within a voxel (Good et al, 2001).…”
Section: Methodsmentioning
confidence: 99%